Optimal money creation in "pure currency" economies: a conjecture. (15th October 2013) - Wallace, Neil
Abstract: In a pure-currency economy, money is the only durable object and people have private histories. In such economies, taxation is not feasible and in some of them trade is enhanced through the use of money. For economies of that kind in which a nondegenerate distribution of money, part of the state of the economy, affects trades and real outcomes, and in which trades affect the state at the next date, the conjecture is that there are transfer schemes financed by money creation that improve ex ante representative-agent welfare relative to what can be achieved holding the stock of money fixed.